2010
DOI: 10.1213/ane.0b013e3181c4bab7
|View full text |Cite
|
Sign up to set email alerts
|

The First Scintigraphic Detection of Tumor Necrosis Factor-Alpha in Patients with Complex Regional Pain Syndrome Type 1

Abstract: Tumor necrosis factor (TNF)-alpha has been identified as a pathogenic factor in many immunologically based diseases and complex regional pain syndrome (CRPS). In this case series, we used radiolabeled technetium anti-TNF-alpha antibody to scintigraphically image TNF-alpha in 3 patients with type 1 CRPS. The results show that TNF-alpha was localized only in affected hands of patients with early-stage CRPS. No uptake was seen in clinically unaffected hands and late-stage CRPS. Our findings support the growing ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 17 publications
0
14
0
1
Order By: Relevance
“…Intriguingly, inflammatory cytokines such as TNF-α and IL-6 are up-regulated in CRPS skin and skin blister fluid. 2, 17, 19, 20, 23 Recently we observed that in patients with early CRPS there is keratinocyte proliferation in the affected skin and these activated keratinocytes express TNF-α and IL-6. 4 Similarly, at 4 weeks after fracture/casting in rats the hindpaw skin keratinocytes proliferate and express increased levels of TNF-α, IL-1β, IL-6, and NGF in the hindpaw skin.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, inflammatory cytokines such as TNF-α and IL-6 are up-regulated in CRPS skin and skin blister fluid. 2, 17, 19, 20, 23 Recently we observed that in patients with early CRPS there is keratinocyte proliferation in the affected skin and these activated keratinocytes express TNF-α and IL-6. 4 Similarly, at 4 weeks after fracture/casting in rats the hindpaw skin keratinocytes proliferate and express increased levels of TNF-α, IL-1β, IL-6, and NGF in the hindpaw skin.…”
Section: Discussionmentioning
confidence: 99%
“…21 Furthermore, TNF-α levels are increased in CRPS skin biopsies when measured by enzyme immunoassay and in CRPS affected hands scintigraphically imaged with radiolabeled anti-TNF-α antibody. 1, 24 …”
Section: Introductionmentioning
confidence: 99%
“…These depolarizations trigger the release of neuropeptides such as CGRP and substance P (SP), which induce local inflammation, protein extravasation, vasodilatation, and the release of cytokines [18]. Accordingly, skin levels of SP, CGRP, and inflammatory cytokines are elevated in CRPS [2,20,23,28]. Tissue hypoxia in itself may also elicit inflammation by up-regulating nuclear factor-jB transcription [47].…”
Section: Inflammation and Edema In Crpsmentioning
confidence: 99%